PENGARUH PERBANDINGAN PELARUT ETANOL-AIR TERHADAP KADAR TANIN PADA SOKLETASI DAUN GAMBIR (Uncaria gambir Roxb) - Rozanna Sri Irianty; Silvia Reni Yenti (Jurnal Sagu, 2014)
The sale value is measured from tanin levels. Gambier that was produced by society by soaking with waterlevels tanin 37.25 ppm. Sokletasi extraction method give extracts yield higher because of the warming isexpected to improve the solubility of the extract so that obtained extract higher. Tannins are a class ofcompounds which belong to the class of polyphenols that can be found in almost all types of geen plants. Thisstudy did sokletasi gambier leaves with water ethanol solvent composition variation 1;1, 1;2, 1;4 to obtainan extract gambier with tanin highest levels. Treatment includes draining the leaves of gambier , ginding,sifting, sokletasi and evaporation. Subsequently, 5 ml of the filtrate of yield was added FeCl3 to qualitativeanalysis, the rest is evaporated to obtain gambier extract and for quantitative analysis using UV-visspectrophotometer. The results yield the largest gambier leaves extract on ethanol-water 1:2 at 63.7% andthe highest levels of tannins in ethanol-water 1:4 solvent at 94.75 ppm.Key words: gambier leaves, sokletasi, tannins.